2020
DOI: 10.37616/2212-5043.1088
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine And Azithromycin As A Treatment Of Covid- 19: Electrocardiogram Variability

Abstract: During the COVID-19 pandemic, the effectiveness of the combination of hydroxychloroquine and azithromycin is widely discussed. This treatment can cause many severe cardiac side effects that makes us discuss its utility. The aim of this study is to describe the cardiovascular effect of hydroxychloroquine and azithromycin by analyzing surface ECG in patients with COVID-19. This observational cohort study included Moroccan patients with COVID-19 diagnosis and were hospitalized in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…[ 39 ] Several surveys have suggested that patients with COVID-19 have symptoms of depression, insomnia, anxiety,[ 40 41 ] and post-traumatic stress disorder. [ 42 43 ] Coronaviruses may also affect the central nervous system leading to a significant psychiatric and neuro-psychiatric burden among infected individuals in the acute or post-illness stage. This may include neuro-psychiatric conditions such as confusion, impaired memory, insomnia, depression, and anxiety in individuals who have survived the severe illness.…”
Section: Discussionmentioning
confidence: 99%
“…[ 39 ] Several surveys have suggested that patients with COVID-19 have symptoms of depression, insomnia, anxiety,[ 40 41 ] and post-traumatic stress disorder. [ 42 43 ] Coronaviruses may also affect the central nervous system leading to a significant psychiatric and neuro-psychiatric burden among infected individuals in the acute or post-illness stage. This may include neuro-psychiatric conditions such as confusion, impaired memory, insomnia, depression, and anxiety in individuals who have survived the severe illness.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin, such as many other antiparasitic drugs-ivermectin [205][206][207][208][209], doxycycline [210][211][212], metronidazole [213], mefloquine [214], and hydroxychloroquine [215,216]has been suggested as a possible adjuvant agent in the treatment of coronavirus disease 2019 (COVID-19) infection [217][218][219][220][221]. Due to its anti-inflammatory, antioxidant and potent mitoprotective properties, melatonin might be beneficial in the preservation of mitochondrial functions and neuro-and cardioprotection during infections, whereas clarification of its mechanism of action as antiparasitic agent would be an interesting topic for further research.…”
Section: The Role Of Melatonin In the Treatment Of The Protozoan Parasitic Infectionsmentioning
confidence: 99%